Mapping the Field of Knowledge Management: Bibliometric and Content Analysis of Journal of Information & Knowledge Management for the Period from 2002–2016 - Alajmi, Bibi; Alhaji, Talal (Journal of information & knowledge management, 2018)
This study aims to overview the research trends in Knowledge Management (KM) using a bibliometric and content analysis. Several research questions pertaining to the annual growth of KM publications, the key topics discussed, popular methodologies, country of origin, and citations analysis are posed and answered. In total, 475 articles published in the Journal of Information & Knowledge Management (JIKM) were retrieved from the Scopus bibliographical database. The results showed a relatively steady growth in the number of articles published in JIKM between 2002 and 2016. US scholars authored 21% of the articles published in JIKM, followed by those from India (almost 10%), Australia (8%), and the UK (7.5%). It is also noteworthy that scientific papers published in JIKM are referenced in highly cited journals of computer science, business, and library and information science. Topics such as knowledge discovery, taxonomy and ontology, and knowledge representation were the major KM research trends to arise from the current phenomena of “big data” and data analytics, as reflected in the subject matter of published works. A comparison between the counts for qualitative and quantitative research methodologies showed a clear tendency toward the latter, including questionnaires, while case studies, content analysis, and framework and conceptual papers also proved to be important for KM researchers.